A Survey on Image and Video Dehazing - Thomas, Amla; Azath, M (International Journal of Computer Sciences and Engineering, 2015)
Most of the computer applications use digital images. Digital image processing acts an important role in the analysis and interpretation of data, which is in the digital form. Images and videos of outdoor scenes are mainly affected by the bad weather conditions such as haze, fog, mist etc. It will result in poor visibility of the scene caused by the lack of quality. It will make awful impact on applications like object detection, tracking and surveillance system. One of the major challenges is the restoration of actual original image from the degraded image with at most accuracy. This survey aims to study about various existing methods such as polarization, dark channel prior, depth map based method etc. are used for dehazing.